The extent of the legitimacy of Arab peace treaties with the Zionist enemy entity in Islamic law and man-made legislation - Qushaimh, Hameed Aadm Ali (Arab Journal for Sciences and Research Publishing, 2023)
This research discusses the legitimacy of Arab peace treaties with the Zionist enemy entity in Islamic law and man-made legislation. As these treaties are a real challenge as they represent a breach of the wall of Arab unity, and the Palestinian people and their just cause in particular. What makes matters more complicated are the discrepancies in the positions of some jurists and scholars of Islamic law regarding the peace agreements with the Zionist enemy entity, which are evident through their fatwas. In this study, we will review fatwas and legal rulings issued by jurists and muftis affiliated with the ruling establishment, and others who do not belong to the ruling regime, with an indication of the terms of the treaty considered legally and legally, which are evident by comparing it with the precedent of Hudaybiyah, and the agreements and treaties concluded with the Zionist enemy entity in our present era, from which he extracts: 1- The impermissibility of adhering to the treaty of reconciliation with the Jews; Because it included conditions that are not sanctioned by Sharia or law. It included recognition of the aggressor, his usurpation of Muslim land and their sanctities, and his occupation of their land after forcibly expelling them from it by force of arms. 2- The sanctity of normalization with the Zionist enemy entity in all its forms and forms, as it cannot be measured against the precedent of Hudaybiyyah, nor any treaty concluded by the Messenger, may God bless him and grant him peace, earlier or later; Because he is a usurper of land that does not belong to him. Therefore, this study recommended the following: 1- Serious work to end these peace treaties that were concluded with the Zionist enemy entity, by issuing an internal law criminalizing reconciliation with the Zionist enemy, and then relying on that and directing the United Nations to veto these treaties, as well as documenting war crimes and genocide committed by the enemy. Zionist, against the defenseless Palestinian people, and relying on that to invalidate those treaties. 2- The need to pay attention to the issue of the Palestinian people, as a major issue, by activating the role of the League of Arab States and the Organization of the Islamic Conference to carry out their responsibilities towards the Palestinian people and their just cause.
Keywords: Arab peace treaties; the Zionist entity; their legitimacy